2020
DOI: 10.1111/pan.14075
|View full text |Cite
|
Sign up to set email alerts
|

A quality improvement initiative to improve management of procedural pain in preterm neonates

Abstract: Background Neonates managed in neonatal intensive care units undergo several invasive procedures. However, neonatal procedural pain is not well recognized and managed in most neonatal units. Aims To decrease the severity of procedural pain in preterm neonates (<37 weeks gestational age at birth), as measured by Premature Infant Pain Profile , by 50% by April 2020. Methods A quality improvement initiative was conducted in a level 3 neonatal intensive care unit in South India. The pain was assessed independently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Improvements in staff knowledge, behaviors, and sucrose use were consistent with findings from the literature. Improving the use of analgesic measures improved procedural pain through targeted pain management interventions 13. Increased knowledge of neonatal pain management practices and proper sucrose use resulted in better pain management during PIV insertion procedures 14…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improvements in staff knowledge, behaviors, and sucrose use were consistent with findings from the literature. Improving the use of analgesic measures improved procedural pain through targeted pain management interventions 13. Increased knowledge of neonatal pain management practices and proper sucrose use resulted in better pain management during PIV insertion procedures 14…”
Section: Discussionmentioning
confidence: 99%
“…Improving the use of analgesic measures improved procedural pain through targeted pain management interventions. 13 Increased knowledge of neonatal pain management practices and proper sucrose use Improving Consistency in the Use of Sucrose With Comfort Measures During Minor Painful Procedures resulted in better pain management during PIV insertion procedures. 14 The increase in documented sucrose use with comfort measures during PIV placements was modest.…”
Section: Discussionmentioning
confidence: 99%
“…54 Even more important, when painful procedures, including endotracheal intubation or chest tube placement, are performed, advocating for pain management medications is essential and cannot be replaced with only nonpharmacological interventions. 55 Oral feeding is another action that should be a positive experience for both the infant and parents. While placing the infant directly at the chest for oral feedings is best, infants in the NICU often receive some feedings by bottle.…”
Section: What Can We Do?mentioning
confidence: 99%
“…When skin-to-skin holding is not an option, facilitated tucking has also been shown to reduce stress and pain 54. Even more important, when painful procedures, including endotracheal intubation or chest tube placement, are performed, advocating for pain management medications is essential and cannot be replaced with only nonpharmacological interventions 55…”
Section: What Can We Do?mentioning
confidence: 99%
“…Anne et al 4 in their quality improvement initiative to improve management of procedural pain in preterm neonates concluded that targeted interventions can improve neonatal procedural pain management by improving use of analgesic measures, decreasing the number of procedures and educating and training healthcare personnel. Nana et al 5 have reported that educational interventions like training have modest effect 9.7% (5.5%–21.3%) on improving processes of care in 2018.…”
Section: Introductionmentioning
confidence: 99%